Catastrophic Antiphospholipid Syndrome Presenting as Bilateral Central Retinal Artery Occlusions - Steven S. Saraf; Yogin P. Patel; Ankit Desai; Uday R. Desai (Case Reports in Ophthalmological Medicine)
A previously healthy 22-year-old African American woman presented with bilateral vision loss associated with headache. Her ocular examination was significant for bilateral retinal arterial “boxcarring,” retinal whitening, retinal hemorrhages, and cherry red spots. She was diagnosed with bilateral central retinal artery occlusions and was hospitalized due to concomitant diagnosis of stroke and hypercoagulable state. She was also found to be in heart failure and kidney failure. Rheumatology was consulted and she was diagnosed with catastrophic antiphospholipid syndrome in association with systemic lupus erythematosus. Approximately 7 months after presentation, the patient’s vision improved and remained stable at 20/200 and 20/80.